Metal–Organic Frameworks as Key Materials for Solid-Phase Microextraction Devices—A Review - Adrián Gutiérrez-Serpa; Idaira Pacheco-Fernández; Jorge Pasán; Verónica Pino (Separations, 2019)
Metal−organic frameworks (MOFs) have attracted recently considerable attention in analytical sample preparation, particularly when used as novel sorbent materials in solid-phase microextraction (SPME). MOFs are highly ordered porous crystalline structures, full of cavities. They are formed by inorganic centers (metal ion atoms or metal clusters) and organic linkers connected by covalent coordination bonds. Depending on the ratio of such precursors and the synthetic conditions, the characteristics of the resulting MOF vary significantly, thus drifting into a countless number of interesting materials with unique properties. Among astonishing features of MOFs, their high chemical and thermal stability, easy tuneability, simple synthesis, and impressive surface area (which is the highest known), are the most attractive characteristics that makes them outstanding materials in SPME. This review offers an overview on the current state of the use of MOFs in different SPME configurations, in all cases covering extraction devices coated with (or incorporating) MOFs, with particular emphases in their preparation.